The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1075/tsl.83.14kap
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and the emergence of prefabs: Evidence from monitoring

Abstract: Native English speakers were instructed to detect instances of /√p/ in spoken sentences by pressing a button as soon as they hear /√p/ regardless of whether it is inside another word. We observe that detection of the particle up is slower when the frequency of the verb+up collocation is low or extremely high than when it is medium. In addition, /√p/ is more difficult to detect in high-frequency words than medium-frequency or lowfrequency words. Thus word frequency has a monotonic effect on detectability of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 42 publications
5
45
1
Order By: Relevance
“…Our finding that the mediumfrequency phrasal verbs in our experiment produced a lexical effect contests the hypothesis that only ultra-high-frequent word combinations can be lexically stored (Kapatsinski & Radicke, 2009). …”
Section: The Link Between Verb and Particle Is Lexical Not Syntacticmentioning
confidence: 36%
See 1 more Smart Citation
“…Our finding that the mediumfrequency phrasal verbs in our experiment produced a lexical effect contests the hypothesis that only ultra-high-frequent word combinations can be lexically stored (Kapatsinski & Radicke, 2009). …”
Section: The Link Between Verb and Particle Is Lexical Not Syntacticmentioning
confidence: 36%
“…go up, keep up, line up). The experiments revealed a reduced ability to detect up within frequent words but speeded recognition in frequent verb-particle contexts; only for extremely frequent verb-particle combinations could a behavioural pattern be observed similar to that seen for single words (i.e., difficulty to detect a part within the whole, Kapatsinski & Radicke, 2009). These psycholinguistic results suggest that the large majority of verb-particle combinations are processed differently from single words, except for a few extremely frequent combinations, such as go up or set up (1531 and 8483 occurrences, respectively, in the 100 million word British National Corpus).…”
Section: A Neurophysiological Perspective On Linguistic Linkagementioning
confidence: 99%
“…an infinitive clause). Kapatsinski and Radicke (2008) argue for competition between larger units and their parts when the whole-form is of sufficient frequency. Participants had to respond whenever they detected the particle 'up' in a verb-particle combination (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, Kapatsinski and Radicke (2009) found that the sound sequence /ʌp/ was more difficult to detect in a monitoring task when it was em bedded in a highfrequency word compared to when it was embedded in a low frequency word. Kapatsinski and Radicke used these data to argue that frequent words may be perceived as unitized wholes, making their parts harder to detect (see also Bybee 2001;Hay 2003;Healy 1976;Kapatsinski 2010b for similar pro posals).…”
Section: Frequency Probability and Primingmentioning
confidence: 97%